Application of a Simple In-House PCR-SSP Technique for HLA-B* 27 Typing in Spondyloarthritis Patients. (19th December 2013) - Parasannanavar, Devraj J.; Rajadhyaksha, Anjali; Ghosh, Kanjaksha
Abstract : Background . Microlymphocytotoxicity (MLCT) and flowcytometry (FC) are the conventional serological methods to detect HLA-B* 27. Due to some disadvantages in these methods, most of the HLA laboratories have now switched over to molecular methods. Molecular techniques based on commercial kits are expensive; as such many laboratories with limited funds in developing countries cannot afford these techniques. Aims . Our main aim was to standardize a simple inexpensive in-house PCR-SSP technique for HLA-B* 27 typing. Materials and Methods . Sequence Specific primers were designed to amplify all the subtypes of B* 27 using IMGT-HLA sequence database. Accuracy was checked by retyping of 90 PCR-SSOP typed controls. Results . The presence of 149 bp specific band with control band on 2% agarose gel showed B* 27 positivity. No discrepancies were found when compared with PCR-SSOP results. The frequency of HLA-B* 27 was found to be significantly increased (68.75% versus 4.40%, O.R 46.909: P value 6.62 E - 32 ) among 700 SpA patients as compared to controls. Clinically, 54% of patients had polyarticular arthritis with SI joints involvement (68%) and restricted spine flexion (60%). Conclusion . In-house PCR-SSP technique is very simple and inexpensive technique to detect B* 27 allele, which was strongly associated with SpA patients from Western India.